Zagrożenia i ochrona podatności na zmiany i innowacyjność pracowników w warunkach redukcji personelu - Wrzosek, Krystyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Restructurization activities joined with personnel reduction cause many negative effects. The author discusses how to neutralize those effects in social sphere of employees who stay in the enterprise, so that they do not reduce receptivity to change and commitment to carry out restructurization activities -especially in management system. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 364-373